An insight into the commercial viability of green roofs in Australia - Tassicker, N.; Rahnamayiezekavat, Payam; Sutrisna, Monty (MDPI AG, 2016)
Construction industries around the world have, in recent history, become increasingly concerned with the sustainability of building practices. Inherently, the development of the built environment results in partial or complete destruction of the natural environment. Advanced European and North American countries have turned to green roofs as a means of sustainable development. Australia, on the other hand, has yet to fully realize the potential of green roof technology. In the first case, an extensive review of green roof literature was undertaken to establish the dominant perspectives and over-riding themes within the established body of international literature. The collection of primary data took the form of qualitative, semi-structured interviews with a range of construction practitioners and green roof experts; landscape architects, consultants and academics. The information gained from the interviews facilitated the primary aim of the paper; to critically analyse the state-of-practice in the Australian green roof industry. Green roofs, despite their proven sustainability benefits and their international success, have experienced a relatively sluggish uptake in the Australian construction industry. With this being said, the Australian green roof industry is considered to have promising potential for the future; should there be legislative changes made in its favour or greater education within the industry. To advance the local industry, it was found that government authorities are required to adapt policy settings to better encourage the use of green roofs, whilst industry bodies are required to host better, more targeted educational programs.